Investigate the effects of incorporation of powdered form plastic as partial cement replacement on the performance of concrete - Pan, De Wei (2022)
Plastic waste is a major component of the global waste stream. The accumulation of vast amounts of plastic waste has led to numerous environmental problems due to its non-biodegradable nature. At the same time, cement manufacturing releases an enormous amount of carbon dioxide into the atmosphere. This research suggested the incorporation of plastic waste in powder form as partial cement replacement in the manufacturing of concrete. Using plastic waste as a replacement for cement will reduce the amount of plastic waste and the demand for cement. As a result, the environmental impact of plastic waste and cement will be lowered. This research replaced a partial amount of cement with plastic waste powder at 4%, 8%, 12%, and 16% by cement weight. The type of plastic waste used in this study is PVC plastic. A total of eight types of tests were conducted to determine the properties of concrete, including slump test, compressive strength test, flexural strength test, porosity test, water absorption test, gas permeability test, chloride penetration test, and SEM-EDX analysis. The experimental results revealed that the workability of concrete with substitution of PWP as partial cement replacement is increased. The concrete specimen with 16% of cement being replaced by PWP obtained the highest workability in this study which is 63 mm. In addition, the mechanical and durability properties of the concrete specimen with 4% of cement being replaced by PWP are similar to the control specimen, which does not contain any PWP. The highest compressive strength of concrete can be produced from this study after being cured for 28 days is 22.88 MPa when 4% of PWP used to partially replace cement. However, the further increment of PWP substitution will reduce the mechanical and durability properties of concrete. Moreover, the cost of manufacturing the 1 m3 concrete with 4% PWP as cement substitution is RM 215.42 which is lower than the conventional concrete (RM 210.9).